57 Invasive versus medical management of elderly patients with non-ST elevation myocardial infarction (NIHR Health Informatics Collaborative Senior-NSTEMI study). (May 2019) - Kaura, Amit; Sterne, Jonathan; Mulla, Abdulrahim; Panoulas, Vasileios; Glampson, Ben; Davies, Jim; Woods, Kerrie; Omigie, Joe; Shah, Anoop D; Channon, Keith; Weber, Jonathan N; Thursz, Mark R; et al.
Abstract : Background: Trials and registry studies suggest lower long-term mortality after invasive than medical management among patients with non-ST elevated myocardial infarction (NSTEMI), but elderly patients were underrepresented. The aim of our study was to estimate the effect of invasive compared with medical management on survival in patients with NSTEMI aged ≥80 years, using routine clinical data. Methods: We used National Institute for Health Research Health Informatics Collaborative data to identify eligible patients admitted during 2010–2017 at five tertiary centres. We compared patients who did and did not have invasive management within 3 days of their peak troponin level. To limit the effect of immortal time bias, follow-up started 3 days after peak troponin: deaths within three days were excluded. We conducted intention-to-treat analyses. Propensity scores were derived from a logistic regression model based on pre-treatment variables: patient demographics, blood test results, cardiovascular risk factors, history of cardiovascular disease and other comorbidities. We modelled non-linear relationships using splines. Patients with high probability (based on propensity score) of medical or invasive intervention were excluded. We used Cox models to estimate hazard ratios (HR) comparing invasive with medical management. Three methods were used to control confounding; multivariable-adjusted, multivariable-adjusted additionally for continuous propensity score and inverse-probability-of-treatment (IPT) weighting. Kaplan-Meier survival curves were plotted. The robustness of the results to unmeasured confounding was assessed in sensitivity analyses. Results: The 1, 636 patients (59.8% medical management) included in analyses had a median age of 85 (IQR 82–89) years. During a median follow-up of 32.4 (IQR 11.5–53.9) months, there were 717 (43.8%) deaths. At 3-years, cumulative survival was 76.9% and 53.6% in the invasive and medical management groups, respectively (figure 1 ). The crude HR comparing invasive with medical management was 0.41 (95% CI 0.34–0.50). The multivariable-adjusted HR was 0.51 (95% CI 0.42–0.63), was 0.50 (95% CI 0.40–0.61) with additional adjustment for propensity score, and was 0.54 (95% CI 0.48–0.61) in the IPT-weighted model (all p<0.0001). The E-value for the point estimate was 2.61: this implies that residual confounding could explain the association if there is an unmeasured covariate with a relative risk of at least 2.61 for both mortality and undergoing invasive management. The highest mortality HR for comorbidities included in our model were heart failure (HR 2.06 (95% CI 1.60–2.63)) and aortic stenosis (HR 1.95 (95% CI 1.42–2.67)). Conclusion: This study provides evidence that the survival advantage from invasive management may extend to elderly patients with NSTEMI. Future research should address the possibility of unmeasured confounding, including by post-admission prognostic factors that affect choice of invasive or medical management. Conflict of Interest: No conflict of interest